The Reciprocal Connection Between Identity and Consumption: A Literature Review - Benjamin Sassonko (Junior Management Science (JUMS), 2020)
Consumer identity has been an integral part of marketing and psychology research for decades, resulting in an extensive stream of literature. The main purpose of this paper is twofold: First, to accentuate the reciprocity between identity and consumption, a relationship that has been insufficiently addressed in marketing literature. Second, the core papers in this field are reviewed to propose an overarching framework for grouping past and future research. The paper identifies three fundamental concepts that are at the core of the framework: (1) Identity Construction: the process of mentally forming one's identities that constitute the self-concept; (2) Self-Expression Through Consumption: conscious and strategic consumption decisions for identity-expression; and (3) Identity-Effects on Judgments: static effects of chronically salient identities and dynamic effects of primed identities on decisions. This framework will help identify potential avenues for future research.
Keywords: 650; Identity consumption reciprocity; Consumer behavior; Consumer identity; Consumer identity literature review